A Study And Analysis Of The Plurality Of Views Among Scholars And Experts In Hadith Studies Regarding The Validity Of Dhaif Hadiths - Wahid, Abdul; Darniati, Darniati; Amin, Muhammad; Yahya, Agusni (Al-Bukhari : Jurnal Ilmu Hadis, 2023)
Hadith for Muslims has a very important position, because it reveals various traditions that developed at the time of the Prophet Muhammad which were full of various Islamic teachings. Understanding hadith is very important because hadith is the legal basis after the Qur'an, so its validity must be ensured, it is important to study the science of hadith or the blasphemy of a hadith, especially in this case the blasphemy of dhaif hadith, because hadith is the second source of law used by Muslims in determining or deciding a law. As intellectuals, we should show progress in the field of science, especially in the field of religion so that we don't make mistakes in implementing it in life. The purpose of this study is to explain the blasphemy of dhaif hadiths among muhaddisin scholars. The research method used is library research with data collection techniques through good documentation from books, journals, articles and other sources that discuss the blasphemy of dhaif hadiths. The findings of the research show that, in general, the scholars reject it as evidence and the scholars also agree to prohibit the narration of dhaif hadiths that are maudhu' without mentioning their willingness. But if the dhaif hadith is not a maudhu hadith, then there is still a dispute about whether or not it is permissible to narrate it for hujjah